2019
DOI: 10.1371/journal.pone.0226116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quantitative trait locus mapping of late-flowering from a Thai soybean cultivar introduced into a photoperiod-insensitive genetic background

Abstract: The timing of both flowering and maturation determine crop adaptability and productivity. Soybean (Glycine max) is cultivated across a wide range of latitudes. The molecular-genetic mechanisms for flowering in soybean have been determined for photoperiodic responses to long days (LDs), but remain only partially determined for the delay of flowering under short-day conditions, an adaptive trait of cultivars grown in lower latitudes. Here, we characterized the late-flowering (LF) habit introduced from the Thai c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Indeed, a recent study demonstrated that after J , E1 has the next most important effect on time to maturity in tropical environments (Miranda et al, 2020). Finally, GmFT2a may also have been a target for delayed flowering, as a non‐synonymous amino acid substitution in exon 4 is tightly associated with late flowering (Jiang et al, 2019; Ogiso‐Tanaka et al, 2019; Sun et al, 2019).…”
Section: Adaptation Of Soybean To Different Latitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent study demonstrated that after J , E1 has the next most important effect on time to maturity in tropical environments (Miranda et al, 2020). Finally, GmFT2a may also have been a target for delayed flowering, as a non‐synonymous amino acid substitution in exon 4 is tightly associated with late flowering (Jiang et al, 2019; Ogiso‐Tanaka et al, 2019; Sun et al, 2019).…”
Section: Adaptation Of Soybean To Different Latitudesmentioning
confidence: 99%
“…More recently, several other flowering time loci were shown to encode members of the well‐known FT (florigen) protein family. These FT homologs belong to the phosphatidylethanolamine binding protein (PEBP) family (Wang et al, 2015) and serve as major points of integration in flowering time control (Takeshima et al, 2016; Jiang et al, 2019; Ogiso‐Tanaka et al, 2019; Sun et al, 2019). Many FT genes are expressed in leaves under flower‐inducing conditions.…”
Section: Classical Flowering Loci and Their Molecular Identitiesmentioning
confidence: 99%
“…A reduction in ambient temperature from 22 to 16 • C delays flowering in Arabidopsis (Strasser et al, 2009). This process involves a number of molecular mechanisms: (1) the occupation of histone H2A variant H2A.Z nucleosomes on the FT locus to inhibit the binding of the PIF4 transcription factor to the promoter, (2) destabilization of the CO protein by HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES 1, an E3 ubiquitin ligase, and (3) repression of floral integrators (FT, TWINSISTER OF FT, and SUPPRESSOR OF CONSTANS OVEREXPRESSION 1) by repressor complexes of SHORT VEGETATIVE PHASE with functional transcripts of FLOWERING LOCUS M (FLM-β) and MADS AFFECTING FLOWERING 2 (MAF2ver1) (Ratcliffe et al, 2003;Strasser et al, 2009;Jung et al, 2012;Gu et al, 2013;Lee et al, 2013;Posé et al, 2013;McClung et al, 2016;Song, 2016). The evening complex, which consists of ELF3, ELF4, and LUX ARRHYTHMO (LUX), represses its direct targets, PSEUDO RESPONSE REGULATOR 7 (PRR7), GI, and LUX, and delays flowering under cool temperatures (Mizuno et al, 2014).…”
Section: Col2b Is a Candidate For Flowering Repression By Cool Tempermentioning
confidence: 99%
“…The evening complex, which consists of ELF3, ELF4, and LUX ARRHYTHMO (LUX), represses its direct targets, PSEUDO RESPONSE REGULATOR 7 (PRR7), GI, and LUX, and delays flowering under cool temperatures (Mizuno et al, 2014). The loss of function of ELF3 mitigates the repression of flowering by cool temperatures to accelerate flowering under these conditions (Strasser et al, 2009). TERMINAL FLOWER 1 (TFL1) also functions in the control of flowering as a thermal sensor; ELF3 and TFL1 confer the thermal regulation of flowering through different interactions with the PHYTOCHROME B and CRYPTOCHROME photoreceptors (Strasser et al, 2009).…”
Section: Col2b Is a Candidate For Flowering Repression By Cool Tempermentioning
confidence: 99%
See 1 more Smart Citation